ANALISIS PERENCANAAN PENDIDIKAN BERBASIS ASESMEN KEBUTUHAN KURIKULUM MERDEKA DI SMKN 1 SIMPANG EMPAT - Adi Saputra, Riski; Murhartoyo; Suhaimi; Sulistiyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze needs assessment-based educational planning in the implementation of the Merdeka Curriculum at SMK Negeri 1 Simpang Empat. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, limited participatory observations, and document analysis of the School Operational Curriculum (KOSP), School Work Plan (RKS), School Activity and Budget Plan (RKAS), and industry partnership documents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing and verification. The findings reveal that educational planning has been conducted in a participatory and data-driven manner through school self-evaluation, tracer studies, and feedback from industry partners. The integration of needs assessment results into planning documents demonstrates vertical alignment between vision, programs, and budgeting. However, long-term labor market projections and outcome-based performance indicators require further strengthening. This study contributes to the development of adaptive and reflective vocational education planning models oriented toward graduate relevance and employability.